Verification of Computing Grids with Special Edge Conditions by Infinite Petri Nets - D. A. Zaitsev (Modelirovanie i Analiz Informacionnyh Sistem, 2015)
A technique of the computing grid verification using invariants of infinite Petri nets was presented. Models of square grid structures in the form of parametric Petri nets for such edge conditions as connection of edges and truncated devices were constructed. Infinite systems of linear algebraic equations were composed on parametric Petri nets for calculating p-invariants; their parametric solutions were obtained. P-invariant Petri nets are structuraly conservative and bounded that together with liveness are the properties of ideal systems. Liveness investigation based on siphons and traps can be implemented by using p-invariants of modified nets.